Electromagnetic and electrical studies in and around Schirmacher oasis, Antarctica by Indian Antarctic scientific expeditions - Bhattacharya, Bimalendu B. (Polar Science, 2018)
Transient electromagnetic (TEM), vertical electrical soundings (VES) and self-potential (SP) measurements were carried out in Schirmacher Oasis and in the adjoining shelf ice regions of Antarctica in the year 1984. TEM measurements with MPPO system of varying square loops were employed to measure thickness of shelf ice in the neighbourhood of “Dakshin Gangotri” station (since abandoned) which was estimated of the order of 100 m. The thickness of the ice cap in the vicinity of oasis, however, was found to be of the order of 400 m. VES and SP measurements were carried out in Schirmacher oasis in the vicinity of the “Maitree” station. VES measurements showed that the thickness of scree varied from 1.0 m to 2.5 m and the resistivity in the range of 50 Ω-m to 125 Ω-m. The thickness of weathered zone varied widely between 4.9 m and 21.5 m with resistivity varying in the range of 215 Ω-m to 450 Ω-m. The basement resistivity varied ranging from 700 Ω-m to 2,25,000 Ω-m. The purpose of SP measurements was to study the nature of SP processes in the oasis which remains in the subzero condition round the year. SP profiles in the oasis are featureless. SP measurements were made also to examine the possibility of reliable electric field measurements for determining the impedance of the ground, as a guideline, for future magnetotelluric (MT) measurements over the oasis for crustal studies. The Ground Penetrating Radar (GPR) survey detected the entrance shaft of size 95 cm × 99 cm at a depth of 2.00 m of the buried Dakshin Gangotri hanger, built in 1984–85. Magnetotelluric investigations subsequently made over the Schirmacher oasis indicate cratonic-type crust. journal article